2015
DOI: 10.1016/j.amepre.2015.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Quality of Americans by Supplemental Nutrition Assistance Program Participation Status

Abstract: Context The Supplemental Nutrition Assistance Program (SNAP) is an effective component in reducing food insecurity in the U.S. In the discussion of strategies to also help SNAP participants maximize diet quality, it is important to know their current dietary patterns and food choices. This paper provides a systematic review of recent U.S. studies on dietary quality, food consumption, and spending among SNAP participants as compared to income-eligible and higher-income nonparticipants. Evidence acquisition Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
148
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(156 citation statements)
references
References 31 publications
(97 reference statements)
7
148
1
Order By: Relevance
“…To date, nearly all of this research has used self-report measures of dietary intake (11). Household food-purchase data, which are generated when participants scan the barcodes of the products that they have purchased and brought home, can provide a useful complement to self-reported dietary intake data.…”
Section: Introductionmentioning
confidence: 99%
“…To date, nearly all of this research has used self-report measures of dietary intake (11). Household food-purchase data, which are generated when participants scan the barcodes of the products that they have purchased and brought home, can provide a useful complement to self-reported dietary intake data.…”
Section: Introductionmentioning
confidence: 99%
“…For example, if SNAP leads people to a diet high in refined carbohydrates (e.g., white sugar and flour), resulting in a chronic state of hyperinsulinemia (high blood insulin), increased fat deposition, and decreased physical activity, then RMR could decline causing weight to increase even if energy consumption had not changed (Khan and Flier, 2000;Taubes, 2008;Wells and Siervo, 2011). The evidence on differences in diet quality between SNAP participants and income-eligible non participants does not support this hypothesis (Andreyeva et al, 2015), and as we show below, we do not find that participants were gaining weight.…”
Section: Does Snap Participation Affect Energy Balance?mentioning
confidence: 76%
“…However, a recent systematic review of the evidence on the differences in energy consumption, dietary patterns (e.g., sugar sweetened beverage consumption), and diet quality between SNAP participants and income eligible non-participants found mixed results and no conclusive evidence that participation changes dietary patterns for the worse (Andreyeva et al, 2015).…”
Section: Previous Work On Obesity and Snap Participationmentioning
confidence: 95%
“…This could be related to the underlying socioeconomic disparities in food intake and physical activities. A recent review found that low-income children who participated in the Supplemental Nutrition Assistance Program (SNAP) consumed a poorer diet than higher-income non-participating children (Andreyeva et al, 2015). Another review of adolescent physical activity by socioeconomic status indicated that adolescents with higher SES had more physical activities than those with low SES, although discordant findings also existed (Stalsberg and Pedersen, 2010).…”
Section: Introductionmentioning
confidence: 97%